2005
DOI: 10.1097/01.jom.0000150204.12937.f5
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of Health and Safety Training Among Young Latino Construction Workers

Abstract: Results of this research, especially the relatively low level of English communication skills among young Latino workers, point to the need for increased bilingual services not just in worker safety training programs, but also in medical clinics and emergency rooms that treat Latino workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 7 publications
(9 reference statements)
1
67
0
Order By: Relevance
“…Several authors have suggested that language ability is a possible factor, both in terms of safety training and in daily communication on the job (17,19,21,26). This relationship may also work in reverse; Nuwayhid and his colleagues (11) suggested that one possibility for the nondifferential results in their study was that approximately 80% of the injured nonnative workers were Arabic speakers, like the native Lebanese to whom they were compared.…”
Section: Occupational Injuriesmentioning
confidence: 89%
See 1 more Smart Citation
“…Several authors have suggested that language ability is a possible factor, both in terms of safety training and in daily communication on the job (17,19,21,26). This relationship may also work in reverse; Nuwayhid and his colleagues (11) suggested that one possibility for the nondifferential results in their study was that approximately 80% of the injured nonnative workers were Arabic speakers, like the native Lebanese to whom they were compared.…”
Section: Occupational Injuriesmentioning
confidence: 89%
“…The authors suggested that this finding may have been due to a lack of understanding of the training provided, as 25% of those who had been trained received it only in English (21). In another study of immigrant Latino construction workers, a higher proportion, 72%, reported receiving training, but the median length of that training was only 1 hour, and those with less English ability received less training (26). About half of the female farm workers in Texas reported having received pesticide safety training according to the worker protection standard, most of which took place in Spanish (38).…”
Section: Prevention-safety Education Training and Personal Protectivmentioning
confidence: 94%
“…It is believed that training activity is the key in assisting employees to become familiar with the existing safety procedures and policies at the working environment [14]. One could say that there is success in safety training when the employees not only follow the safety rules and regulation but also practice them in their work to ensure their safety [17], [18]- [19]. Lately, trained employees in organization is looked upon as competitive advantage, thus all employees regardless of the level of their work risk will be given safety training [20].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggests that one factor driving immigrant workers' injury risk may be employment in occupations for which they are overqualified (Premji and Smith, 2012). Higher injury risk has also been linked to a lack of appropriate training, poor Englishlanguage skills, and "newness" to the workforce (Corvalan et coll., 1994 ;Dong and Platner, 2004 ;Pransky et al, 2002 ;O'Connor et al, 2005). Finally, several studies have pointed to difficulties immigrants have after a work-related injury.…”
mentioning
confidence: 99%